Pregnancy, Birthing, and Postpartum Experiences During COVID-19 in the United States - DeYoung, Sarah E.; Mangum, Michaela (Frontiers in Sociology, 2021)
The research aims of this project were to understand the impact of the COVID-19 pandemic on pregnancy, birthing, and postpartum experiences in the United States. Our data include responses from 34 states within the US. Findings from our analyses indicate that higher perceived social support predicted higher scores of well-being, while higher scores of perceived loneliness predicted lower scores of well-being, and higher trauma predicted lower well-being measured as satisfaction with life. Qualitative data support these findings, as well as the finding that there were various sources of stress for respondents during pregnancy, birth, and the postpartum timeframe—particularly in terms of managing work/occupation obligations and childcare. Additionally, this research fills a gap in understanding infant feeding in emergencies. Respondents perceived that early release from the hospital reduced access to lactation support, and many respondents reported receiving free samples of breastmilk substitutes through a variety of sources.